Observaciones y capturas de aves poco conocidas en el norte de Argentina - Capllonch, Patricia; Alderete, Carlos A.; Aráoz, Rodrigo; Barboza, Exequiel; Mamaní, Julio C.; Ortiz, Diego; Pérez Bogado, Walter E.; Quiroga, Oscar B.; Soria, Karina (Nuestras Aves, 2015)
Este artículo no cuenta con un resumen.